2020
DOI: 10.3390/app10030845
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Influence of Helical Milling Parameters on the Quality of Holes in the UNS R56400 Alloy

Abstract: Helical milling has been positioned as an alternative to conventional drilling, where the advantages it offers make it very attractive for use on difficult-to-machine alloys such as the titanium alloy UNS R56400. However, the correlation between the indicator of hole quality and the kinematic parameters has rarely been studied. The kinematics are what bring most advantages and that is why it is necessary to know their influence. In this aspect, there are different focuses of problems associated with the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…From 1.5 mm to 2 mm, tool wear increased in a linear fashion. The effect was in line with findings of Puerta-Morales et al [39] during helical milling of titanium alloy UNS R56400. However, the tangential feed (see Figure 5b) affected tool wear significantly.…”
Section: Parametric Analysissupporting
confidence: 92%
“…From 1.5 mm to 2 mm, tool wear increased in a linear fashion. The effect was in line with findings of Puerta-Morales et al [39] during helical milling of titanium alloy UNS R56400. However, the tangential feed (see Figure 5b) affected tool wear significantly.…”
Section: Parametric Analysissupporting
confidence: 92%
“…After having shown and discussed data in detail in the previous paragraphs, a resuming table with synoptic intent is proposed; for this reason, data were treated with ANOVA [30,31]. In Table 3, the results of the p-value confirm that some significative microstructural differences arise due to the adoption of casting additives.…”
Section: Data Treatment With Anovamentioning
confidence: 99%
“…A recent report suggested that down milling, coupled with higher tangential feed, helped improve the surface finish. But the authors were unable to effectively analyze the influence of process parameters on burr formation [31]. Further, the analysis of surface roughness and chip morphology analysis while machining Ti-6Al-4V and Ti-6Al-7Nb titanium alloys showed that Ti-6Al-7Nb presented lower roughness as compared to Ti-6Al-4V alloy at a lower axial pitch and feed values [32].…”
Section: Introductionmentioning
confidence: 98%